Primary somatosensory contextual modulation is encoded by oscillation frequency change. Issue 9 (September 2015) - Götz, T.; Milde, T.; Curio, G.; Debener, S.; Lehmann, T.; Leistritz, L.; Witte, O.W.; Witte, H.; Haueisen, J.
Highlights Very early somatosensory evoked responses show context-dependent modulation by auditory stimuli. Our delay differential equation model strongly suggests cortico-thalamic feedback in primary somatosensory processing. Frequency encoding, in contrast to network coupling, seems to play an important role in contextual modulation in the somatosensory thalamo-cortical network.